KONSEPSI MOTIVASI KERJA DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN - Mukrodi Mukrodi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Motivation is the most important factor to support the nets of a performance activity in order to increase company productivity. Providing motivation to employees is an obligation and is one part of the implementation of human resource management. Every company must have a program that has been designed in a vision and mission, both short-term programs, medium-term programs, and long-term programs. This study aims to identify the factors that motivate employees in carrying out their work, as well as find a new solution regarding expectations about the company's future. This study uses a qualitative method in which the data collection is done by interview so that it can dig deeper about the employee. As the object of this research are the employees of PT. ISS Jasa Indonesia. The results obtained from this study stated that an employee's work motivation is influenced by economic factors that are formed from work values, biographical characteristics, and personal characteristics of the informants